IMPLEMENTASI ZAKAT FITRAH TANPA MELIBATKAN AMIL ZAKAT - Imatun Muawanah; Suad Fikriawan; Khoirul Fathoni (Social Science Academic, 2023)
Zakat is one of the pillars of Islam. The formulation of the problem in this study is: 1. How is the implementation of zakat fitrah without involving amil zakat? 2. How is the law of zakat fitrah without involving amil zakat? Research Method: Qualitative approach, comparative type. The presence of researchers as pure observers and participant observers. Data collection techniques: in-depth interviews, in-depth observation, and documentation. Data analysis techniques: reduction, display and conclusion. Checking data validity: Credibility, dependability and confirmability. The conclusions are as follows: 1). Implementation of zakat fitrah without involving amil zakat as follows, a. The community distributes their zakat directly to orphans and orphanages. b. The community distributes its zakat to widowed mothers. c. The community distributes its zakat to elderly parents who have no relatives. 2) The law of zakat fitrah without involving amil zakat is as follows: Permissible or SAH. Zakat is paid directly and without going through the Amil Zakat Committee, if the recipient of the zakat is included in the category 8 of the Mustahiq zakat group. However, it is more Afdhol if zakat is channeled through a legitimate zakat committee. B. Not Allowed or NOT LEGAL. Zakat is paid directly and without going through the Amil Zakat Committee, if the recipient of the zakat is not included in the category 8 of the Mustahiq zakat group and is just random.